Diverse Physiological Roles of Kynurenine Pathway Metabolites: Updated Implications for Health and Disease - Yuechang Wang; Yonggang Zhang; Wei Wang; Yanmin Zhang; Xueqian Dong; Yang Liu (Metabolites)
Tryptophan is an essential amino acid critical for human health. It plays a pivotal role in numerous physiological and biochemical processes through its metabolism. The kynurenine (KYN) pathway serves as the principal metabolic route for tryptophan, producing bioactive metabolites, including KYN, quinolinic acid, and 3-hydroxykynurenine. Numerous studies are actively investigating the relationship between tryptophan metabolism and physiological functions. These studies are highlighting the interactions among metabolites that may exert synergistic or antagonistic effects, such as neuroprotective or neurotoxic, and pro-oxidative or antioxidant activities. Minor disruptions in the homeostasis of these metabolites can result in immune dysregulation, contributing to a spectrum of diseases. These diseases include neurological disorders, mental illnesses, cardiovascular conditions, autoimmune diseases, and chronic kidney disease. Therefore, understanding the physiological roles of the KYN pathway metabolites is essential for elucidating the contribution of tryptophan metabolism to health regulation. The present review emphasizes the physiological roles of KYN pathway metabolites and their mechanisms in disease development, aiming to establish a theoretical basis for leveraging dietary nutrients to enhance human health.